Web-Based Employee Recruitment Management System In Pt. Tropic Abadi - Haryanto, Haryanto; Putra, Yudha Surya; Natasyah, Nabillah (APTISI Transactions on Management (ATM), 2020)
In a company, back and forth is largely determined by employees accompanied by increasing technology and science in all fields taking place so rapidly. Similarly, the HRD division at PT. Tropic Abadi when managing employee recruitment activities. Employee recruitment management system that runs at PT. Tropic Abadi is currently not running optimally, namely: through an online recruitment website as a medium to provide a bridge of communication regarding job vacancy information, where the process is less practical and adequate. So that management systems are needed in order to be able to do the process of managing employee recruitment to be faster, more precise, effective, and efficient. This research uses a research methodology that is structured system management through UML (Unified Modeling Language) and the final results achieved from writing this scientific journal are by implementing a web-based system for PT. Tropic Abadi in solving these problems, ranging from the speed of information provided and an easily managed database system.